(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In current study, aim was to estimate the total flavonoid, steroids and tannin content as well as antioxidant activity of hydro alcoholic extract of Piper longum Linn. The hydro alcoholic extract was prepared by using alcohol:water concentration. The total flavonoid content was 5.45+ 0.06 mg E/g, total steroid content was 338.25+ 0.83 mg E/g and total Saponin content 42.57 mg E/g was found in extract. The total flavonoid content was determined by Aluminium chloride colometric complex method using Quarcetin as standard, total steroid content was determined by ferric–chloride complex method using Diosgenin as standaard, total Saponin content was determined by Vanillin sulphuric acid complex method using Diosgenin as standard. The antioxidant activity of hydro alcoholic extract of Piper longum was evaluated using 2,2-diphenyl-1- picyhydrazyl (DPPH) assay method. The hydro alcoholic extract of Piper longum Linn. exhibited % radical scavenging activity for 1000 µg/ml was found to be 26.56 % .